Assessment of exergy delivery of thermal energy storage systems for CSP plants: Cascade PCMs, graphite-PCMs and two-tank sensible heat storage systems. (December 2020) - Riahi, Soheila; Liu, Ming; Jacob, Rhys; Belusko, Martin; Bruno, Frank
Highlights: ɛ-NTU an in-house numerical method for energy and exergy assessment. Exergy delivery of indirect cascade thermal energy storage systems compared with two-tank. Cascade PCM systems can deliver required exergy in a comparable efficiency to two-tank systems. Proposed method provides a means for a first level design and selection of cascade thermal storage systems. Abstract: Alternative cascade systems comprising of three, four, and five PCMs, PCM-graphite-PCM and a graphite system were compared with two-tank sensible heat storage systems. Numerical methods including an in-house code and Fluent were used to predict the transient heat transfer during the charging and discharging processes up to 6 h and 10 h, respectively. Energy and exergy analysis assisted in finding the configuration and size of cascade systems considering the material, temperatures and time constraints. Furthermore, the results of the energy and exergy analysis were used to compare the overall exergy efficiency for a useful work delivery of 680 MWhth to the power block. The exergy destructions due to heat transfer, the heat losses from the storage system during the charging process, and pumping power consumption were taken into account. These results show the high potential of cascade indirect systems of PCMs or graphite-PCMs to supply the required thermal energy to the power block with comparable exergy efficiency to the two-tank system. Moreover, this study presents a means for a first level design and selection of cascade systems to achieve the highest exergy efficiency for a specific exergy delivery bounded by a CSP cycle.